Study on the policy boundary of rational development in high water cut period of medium and low permeability conglomerate reservoir. (December 2018) - Yuemiao, Guo; Longmei, Zhao; Peng, Lv; Wei, Tian; Wenxi, Gao; Dan, Li
Abstract: Using numerical simulation technology, the research and analysis of the rational development policy boundary of high and low water cut period in medium and low permeability conglomerate reservoirs are carried out. According to the research, (1) due to the strong homogeneity of the conglomerate reservoir, the injection water is unevenly propelled, and the remaining oil distribution between the oil and water wells is irregular; (2) the local layer pressure is maintained near the saturation pressure. The highest rate and the best development effect; (3) for medium and low permeability conglomerate reservoirs, the reasonable water injection intensity gradually increases with the increase of water content. For example, when the water content is 80%, the reasonable water injection intensity is 10m3/d/m;, for a water content of 90%, a reasonable water injection strength of 6m3 / d / m (3) for the different formation pressure and water content level of the reservoir, determine the ratio of injection and production, for example, the current formation pressure The oil layer with a water content of 8.0 MPa and a water content of 80% has a reasonable injection-production ratio of 1.05.